2018
DOI: 10.1007/978-3-319-93438-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Prosumers as New Energy Actors

Abstract: This chapter analyses the opportunities that prosumers, as new energy actors, bring to achieving energy security goals in the context of the European Union (EU). In energy governance, there is a progressive top-down diffusion of potential, competences, and leverage across the energy value chain from States and corporate actors towards prosumers. Private and public finance should be attracted and directed to infrastructure schemes that will enable a transition from the traditional centralised power network to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The promotion of the development of renewable energy can help a country to achieve the goal of carbon reduction. Leal-Arcas et al [12] observed the phenomenon that energy will be consumed near where it is produced and discussed the role of prosumers in the future development of renewable energy. Borowski [13] discussed the advantages and disadvantages of two different models of the European electricity market and analyzed the impact of the models of the electricity market on the development of renewable energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The promotion of the development of renewable energy can help a country to achieve the goal of carbon reduction. Leal-Arcas et al [12] observed the phenomenon that energy will be consumed near where it is produced and discussed the role of prosumers in the future development of renewable energy. Borowski [13] discussed the advantages and disadvantages of two different models of the European electricity market and analyzed the impact of the models of the electricity market on the development of renewable energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author from [18] uses an optimum pricing scheme for local electricity trading in µGs considering four particular priorities. In other words, the prosumers become the new actors in local electricity power market, considered as µM [19,20]. A different formulation of the PEST optimization follows a hierarchical framework considering the future energy price uncertainty in [21], information and communication technologies (ICT) in [22], and multi-layer architecture model in [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, we identified the role of the renewable self-consumer, mainly by analyzing the legal acts and preparatory documents, and by employing a case analysis method. The main sources are [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and various pieces of EU legislation.…”
Section: Analysis Of the Concept Of The Renewable Energy Prosumermentioning
confidence: 99%
“…Seeking to pay a lower price for electricity, energy prosumers will be able to modulate their demand. Leal-Arcas et al emphasize that the transformation from consumers to prosumers will affect both small and large consumers [23]. The energy prosumer will also be able to act through intermediaries (like aggregators) rather than directly.…”
Section: The Role Of the Energy Prosumer In The Electricity Marketmentioning
confidence: 99%